Well Interference Analysis of Shale Gas Wells Based on Embedded Discrete Fracture Model. (19th April 2022) - Zhang, Qing
Abstract : Well interference is commonly observed in shale gas reservoirs due to the small well spacing, and it significantly affects the shale gas production. Effective evaluation of well interference is important to increase the gas production of shale gas wells. Previous researches mainly focus on the well interference phenomenon and production optimization using numerical simulation so that the quantitative analysis of shale gas well interference is rare. Therefore, this paper is aimed at analyzing the well interference of shale gas wells through production type curves. First, the complex fracture networks are described by using the embedded discrete fracture model (EDFM). Second, different cases are designed to characterize different types and degrees of well interference in shale gas reservoirs. Third, numerical modelling is conducted to simulate the well interference and its effect on gas production. Fourth, the type curves are obtained to quantitatively analyze and compare the impact of well interference on shale gas production. Results show that well interference caused by hydraulic fractures mainly reduce the gas production of the parent well while the gas production of child well can be increased owing to the larger equivalent stimulated area. The pressure depletion is obvious when the well communication degree becomes higher. Differences can be found from early to late periods by the combination of log-log and Blasingame type curves. This work provides a method for well interference evaluation, and it can be used to obtain well spacing and adjust fracturing parameter in shale gas reservoirs.